2018 Aviation Technology, Integration, and Operations Conference 2018
DOI: 10.2514/6.2018-3991
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Aircraft Fuel Burn Modeling on the Airport Surface

Abstract: Aircraft fuel burn modeling is useful for a range of systems analysis activities. Models such as the FAA's Aviation Environmental Design Tool (AEDT) are widely used to support these activities. Previously, limited availability to thrust and movement data forced AEDT to make several simplifying assumptions, which adversely affect the accuracy of its current fuel burn estimates. This paper identifies first order airport surface fuel burn modeling enhancements in the areas of baseline taxi fuel flow modeling, tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Different works were led to compare physical models, such as the Eurocontrol aircraft performance model: BADA [3], to data-driven models [4]. Clemons et al identified first order enhancements to airport surface fuel burn modeling [5]. Turgut et al used the BADA model to estimate aircraft fuel flow for a three-degree flight-path-angle descent [6].…”
Section: State Of the Artmentioning
confidence: 99%
“…Different works were led to compare physical models, such as the Eurocontrol aircraft performance model: BADA [3], to data-driven models [4]. Clemons et al identified first order enhancements to airport surface fuel burn modeling [5]. Turgut et al used the BADA model to estimate aircraft fuel flow for a three-degree flight-path-angle descent [6].…”
Section: State Of the Artmentioning
confidence: 99%